Simulation of Colonial Building Reconstruction in Jakarta Old Town Through Augmented Reality - Prabawasari, Veronika Widi; Bahar, Yudi Nugraha (UI Scholars Hub, 2022)
Augmented reality (AR) is a trending technology with many potential applications. In architecture, AR can help visualize and document historic buildings by virtual reconstruction. Colonial buildings in Jakarta Old Town are cultural heritage buildings that are vulnerable to damage by aging and environmental factors. The mitigation of this damage as the first step toward restoration is important. The storage and maintenance of records of threatened buildings for posterity are also important. The objective of this study is to develop a methodology for AR-based reconstruction. AR technology is implemented through mobile phones or smartphones. The modeling process is simple and interactive and has potential applications in both education and tourism. The reconstruction method of colonial buildings uses markerless AR and a database of historical knowledge of colonial architecture. The architectural style is identified using the database. Then, an AR-Reconstruction prototype, which provides a visual description of the building reconstruction process using 3D graphics animation models of colonial buildings, is developed. The model reproduces the building in its original condition and actual location. In the trial run, access to building details is delayed. Therefore, in the future, the geometric details and marker quality need to be optimized.